Identifying the Hub Genes and Immune Cell Infiltration in Synovial Tissue between Osteoarthritic and Rheumatoid Arthritic Patients by Bioinformatic Approach - Wang, Junjie; Fan, Qin; Yu, Tengbo; Zhang, Yingze (Current Pharmaceutical Design, 2022)
Background: Osteoarthritis (OA) and rheumatoid arthritis (RA) are two common diseases that result in limb disability and a decrease in quality of life. The major symptoms of OA and RA are pain, swelling, stiffness, and malformation of joints, and each disease also has unique characteristics. Objective: To compare the pathological mechanisms of OA and RA via weighted correlation network analysis (WGCNA) and immune infiltration analysis and find potential diagnostic and pharmaceutical targets for the treatment of OA and RA. Methods: The gene expression profiles of ten OA and ten RA synovial tissue samples were downloaded from the Gene Expression Omnibus (GEO) database (GSE55235). After obtaining differentially expressed genes (DEGs) via GEO2R, WGCNA was conducted using an R package, and modules and genes that were highly correlated with OA and RA were identified. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and protein-protein interaction (PPI) network analyses were also conducted. Hub genes were identified using the Search Tool for the Retrieval of Interacting Genes (STRING) and Cytoscape software. Immune infiltration analysis was conducted using the Perl program and CIBERSORT software. Results: Two hundred ninety-nine DEGs, 24 modules, 16 GO enrichment terms, 6 KEGG pathway enrichment terms, 10 hub genes (CXCL9, CXCL10, CXCR4, CD27, CD69, CD3D, IL7R, STAT1, RGS1, and ISG20), and 8 kinds of different infiltrating immune cells (plasma cells, CD8 T cells, activated memory CD4 T cells, T helper follicular cells, M1 macrophages, Tregs, resting mast cells, and neutrophils) were found to be involved in the different pathological mechanisms of OA and RA. Conclusion: Inflammation-associated genes were the top differentially expressed hub genes between OA and RA, and their expression was downregulated in OA. Genes associated with lipid metabolism may have upregulated expression in OA. In addition, immune cells that participate in the adaptive immune response play an important role in RA. OA mainly involves immune cells that are associated with the innate immune response.
Keywords: immune infiltration